Application of the Support Vector Machine (SVM) Algorithm for the Diagnosis of Diabetic Retinopathy - Yuliadi; Dzil Ikram, Fadhli; Julkarnain, M.; Hamdan, Fahri; Nuryadi, Halid (Brilliance: Research of Artificial Intelligence, 2023)
Diabetic Retinopathy (DR) is a disease whose main cause is complications of diabetes mellitus. High levels of sugar in the blood (glucose) are caused by the pancreas' inability to produce insulin. Prevention of diabetic retinopathy and blindness by carrying out examinations at an early stage and doing them regularly. Currently, doctors still carry out examinations manually so they are prone to errors in examinations. This research aims to build an application to diagnose Diabetic Retinopathy in order to facilitate the work of the medical team and doctors at the eye clinic. In the application creation process, MATLAB is used, while feature extraction uses GLCM and for classification, SVM is used. The results of the research are that doctors and medical teams are helped in carrying out manual patient diagnoses and reduce the occurrence of human error.